Children’s responses to 20th century ‘art’ music, in Portugal and Brazil - Boal-Palheiros, G. (2018)
Several studies have investigated how children of different ages respond to diverse musical styles. Age seems to be a determinant factor in the development of musical preferences. Although many teachers advocate the use of a wide variety of musical styles at different school levels, most of them seem to rarely include 20th century ‘art’ music in their lessons. Very few studies have examined children’s responses to this musical repertoire. In addition, most of the research on children’s musical preferences has been carried out in Europe and North America, with few crosscultural comparisons. This study investigated the responses to and preferences for 20th century ‘art’ music of children from Portugal (n=119) and Brazil (n=135) at two age levels (9-11 and 12- 14). At their local schools, in Porto and Curitiba, they listened to 13 excerpts from 20th century works. They were asked to rate their preferences and describe each excerpt. They also indicated if they knew the composers’ names from a given list. The results suggested that overall both Portuguese and Brazilian children knew very few composers and gave low or moderate ratings to all excerpts. The responses of both groups fell within predictions of most theories of musical preferences, with younger children showing more openness to novel excerpts than older children. Age differences were also evident in both the quantity and the types of verbal descriptions of the excerpts, with younger children producing fewer descriptions than the older ones. Musical characteristics also seemed to play a role in their preferences, as they overall liked or disliked particular excerpts, regardless of age or nationality. Our conclusion is that school aged children are rarely exposed to 20th century ‘art’ music. When listening to it for the first time, many children question whether some excerpts represent ‘real’ music. Thus, they tend to be rather conservative towards this repertoire. Some implications for music education, in both Portugal and Brazil, are drawn at the end of the paper.